2018
DOI: 10.1007/s13300-017-0359-z
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Control and Weight Change Associated with Treatment with Exenatide Compared with Basal Insulin: A Retrospective Study

Abstract: IntroductionThe aim of the study was to compare glycemic and weight change outcomes for type 2 diabetes patients treated with either exenatide once-weekly (EQW) or exenatide twice-daily (EBID) with those patients treated with basal insulin (BI).MethodsRetrospective data (2010–2014) were extracted from the Clinical Practice Research Datalink, a UK primary care database. Patients previously naïve to injectable therapy initiating EQW, EBID, or BI were extracted and matched by propensity score within two analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…We found 22 studies in total of which 12 were commercially funded [13][14][15][16][17][18][19][20][21][22][23][24][25] and 10 were funded by academic/non-profit/government organisations [26][27][28][29][30][31][32][33][34][35]. Six studies were identified through reference searching.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We found 22 studies in total of which 12 were commercially funded [13][14][15][16][17][18][19][20][21][22][23][24][25] and 10 were funded by academic/non-profit/government organisations [26][27][28][29][30][31][32][33][34][35]. Six studies were identified through reference searching.…”
Section: Resultsmentioning
confidence: 99%
“…CIs were narrow for the white ethnicity but wide for the other ethnic groups. For background characteristics, see Table S14 9.3 A medium-sized British 2018 cohort study explored the association with severe hypoglycaemia in those previously naïve to any exenatide therapy vs. basal insulin ± OAD [ 20 ]. No association for exenatide on severe hypoglycaemia was observed, although the absolute rates of hypoglycaemia were higher in the insulin-exposed group compared to exenatide (DNS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exenatide belongs to the glucagon-like peptide-1 receptor agonist (GLP-1RA) class of medications [8], which enhances glucose-dependent insulin secretion, suppresses abnormally increased postprandial glucagon secretion, reduces food intake, and slows down gastric emptying [9,10]. Exenatide can reduce glycated hemoglobin (HbA1c) as well as postprandial blood glucose, while effectively reducing body weight in patients with T2DM [8,[11][12][13][14][15]. Unlike insulin, exenatide dosing does not need to be titrated to blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%